The Relationship Between The Number of Parities and Pregnancy Age with Maternal Anemia - Irul Hidayati; Esti Novi Andyarini (State Islamic University of Sunan Ampel, 2018)
According to the World Health Organization, the anemia prevalence was estimated reach 9% in developed countries, while in developing countries reached 43%. The most-at-risk groups were children and women at fertile age, with an estimated prevalence of anemia in infants at 47%, pregnant women by 42%, and in non-pregnant women t ages 15-49 reached 30%. This was an observational analytic research with cross sectional approach. The purpose was to analyzed the relationship between the number of parity and the pregnancy age with the incidence of maternal anemia. The population in this study were 111 pregnant womens who checked their pregnancy to Public Healt Center (PHC) Kintamani 1 at Bangli regency, the province of Bali. The simple random sampling was used in the research with 87 peoples acted as research sample. Using Rank Spearman Correllation test, it was founded that there was a relationship between the number of parity with the incidence of maternal anemia a low relationship, and there was a relationship between gestational age with maternal anemia incidence with a low degree relationship.